Informing the ecology and conservation of amphibians imperiled by chytridiomycosis - Mosher, Brittany Ann, author; Bailey, Larissa L., advisor; Huyvaert, Kathryn P., advisor; Funk, W. Chris, committee member; Muths, Erin, committee member (Colorado State University. Libraries, 2017)
To view the abstract, please see the full text of the document.